Sex and Aesthetics in Samuel Beckett's Work - Stewart, P. author. aut Link
VIII, 229 p.
Keywords: This book places sex and sexuality firmly at the heart of Beckett. From the earliest prose to the late plays, Paul Stewart uncovers a profound mistrust of procreation which nevertheless allows for a surprising variety of non-reproductive forms of sex which challenge established notions of sexual propriety and identity politics.